2022
DOI: 10.15354/sief.22.or057
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Fit and the Effects of School-wide Positive Behavior Interventions and Supports in High-Need Schools: A Quasi-Experimental Study

Abstract: School-Wide Positive Behavior Interventions and Supports is a framework that aims to improve school culture and climate, students’ behavior and attendance. As the program is largely spreading, comparative studies showing its efficacy on students’ outside the United States are needed. In addition, there is a need for studies examining SWPBIS effects on school climate from all the stakeholders’ point of view, especially students and parents. Moreover, few researches used comprehensive questionnaires including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Existing research has demonstrated that the SWPBIS program promotes the development of effective, reassuring, and positive school environments and climates. Cultural Fit and Effects of School-Wide Positive Behavior Interventions and Supports in High Needs Schools: A Quasi-Experimental Study (Deltour et al 2022) in this issue investigated hundreds of children from four schools in Belgium and concluded that SWPBIS is effective at improving the school environment and reducing bullying by fostering better peer and student-teacher relationships. We hope that this report will stimulate more discussion on the topics of school climate and treatments for student behavior.…”
mentioning
confidence: 99%
“…Existing research has demonstrated that the SWPBIS program promotes the development of effective, reassuring, and positive school environments and climates. Cultural Fit and Effects of School-Wide Positive Behavior Interventions and Supports in High Needs Schools: A Quasi-Experimental Study (Deltour et al 2022) in this issue investigated hundreds of children from four schools in Belgium and concluded that SWPBIS is effective at improving the school environment and reducing bullying by fostering better peer and student-teacher relationships. We hope that this report will stimulate more discussion on the topics of school climate and treatments for student behavior.…”
mentioning
confidence: 99%